A case report and literature review on a large MDM2 negative retroperitoneal/psoas muscle well-differentiated liposarcoma mimicking intramuscular myxoma - Victoria Xie; Guiliang Yu; Amanda Wiggett; Justin Rivard; Miao Lu; Yi Yan (Radiology Case Reports)
Well-differentiated liposarcoma (WDLPS) typically presents as a large soft tissue mass in the retroperitoneal region. Amplification of the MDM2 gene is considered the gold standard for pathologic diagnosis. We present a case of 22 cm large intramuscular mass, located in the psoas muscle of the retroperitoneum. No macroscopic fat was identified on imaging, and the lesion featured extensive myxoid stroma, closely mimicking an intramuscular myxoma on both radiological and histopathological evaluation from biopsy sample. Final diagnosis was however revised to MDM2-negative WDLPS.This case highlights the diagnostic challenge posed by WDLPS with extensive myxoid stroma lacking MDM2 amplification and macroscopic fat on imaging. Accurate diagnosis relies on the integration of clinical, radiologic, and pathologic data, as well as thorough sampling of the tumor.